Bioconversion of distillers’ grains hydrolysates to advanced biofuels by an Escherichia coli co-culture - Fang Liu; Weihua Wu; Mary B. Tran-Gyamfi; James D. Jaryenneh; Xun Zhuang; Ryan W. Davis (Microbial Cell Factories, 2017)
Abstract Background First generation bioethanol production utilizes the starch fraction of maize, which accounts for approximately 60% of the ash-free dry weight of the grain. Scale-up of this technology for fuels applications has resulted in a massive supply of distillers’ grains with solubles (DGS) coproduct, which is rich in cellulosic polysaccharides and protein. It was surmised that DGS would be rapidly adopted for animal feed applications, however, this has not been observed based on inconsistency of the product stream and other logistics-related risks, especially toxigenic contaminants. Therefore, efficient valorization of DGS for production of petroleum displacing products will significantly improve the techno-economic feasibility and net energy return of the established starch bioethanol process. In this study, we demonstrate ‘one-pot’ bioconversion of the protein and carbohydrate fractions of a DGS hydrolysate into C4 and C5 fusel alcohols through development of a microbial consortium incorporating two engineered Escherichia coli biocatalyst strains. Results The carbohydrate conversion strain E. coli BLF2 was constructed from the wild type E. coli strain B and showed improved capability to produce fusel alcohols from hexose and pentose sugars. Up to 12 g/L fusel alcohols was produced from glucose or xylose synthetic medium by E. coli BLF2. The second strain, E. coli AY3, was dedicated for utilization of proteins in the hydrolysates to produce mixed C4 and C5 alcohols. To maximize conversion yield by the co-culture, the inoculation ratio between the two strains was optimized. The co-culture with an inoculation ratio of 1:1.5 of E. coli BLF2 and AY3 achieved the highest total fusel alcohol titer of up to 10.3 g/L from DGS hydrolysates. The engineered E. coli co-culture system was shown to be similarly applicable for biofuel production from other biomass sources, including algae hydrolysates. Furthermore, the co-culture population dynamics revealed by quantitative PCR analysis indicated that despite the growth rate difference between the two strains, co-culturing didn’t compromise the growth of each strain. The q-PCR analysis also demonstrated that fermentation with an appropriate initial inoculation ratio of the two strains was important to achieve a balanced co-culture population which resulted in higher total fuel titer. Conclusions The efficient conversion of DGS hydrolysates into fusel alcohols will significantly improve the feasibility of the first generation bioethanol process. The integrated carbohydrate and protein conversion platform developed here is applicable for the bioconversion of a variety of biomass feedstocks rich in sugars and proteins.